Through your skin to your heart and brain: A critical evaluation of physiological methods in Cognitive Translation and Interpreting Studies - Rojo, Ana María; Korpal, Paweł (Linguistica Antverpiensia, New Series – Themes in Translation Studies, 2021)
This article offers a critical appraisal of two experimental methods used to provide physiological measures of stress and emotions in translation and interpreting research, namely, the analysis of heart rate and heart rate variability, and skin conductance. This is a hands-on introduction to summarize information for fellow-researchers on what these methods are and what they tell us about our body and mind as well as to offer a comprehensive summary of practical applications and analysis standards. The first part of the article introduces the ways in which emotions are experienced and processed in the brain; it provides a framework for interpreting physiological arousal and its role in the perception and construction of emotions. The second part is structured in two parallel sections devoted to each of the two experimental methods. Both sections review existing research on these methods in Translation and Interpreting Studies and discuss the way in which each can best be used in experimental research. They offer suggestions on experiment planning, measurement, data analysis and data reporting. A final remark on ethics and triangulation is offered and some emerging challenges are addressed.